2014
DOI: 10.1152/ajprenal.00675.2013
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells alter macrophage phenotype and promote regeneration via homing to the kidney following ischemia-reperfusion injury

Abstract: Mesenchymal stem cells (MSCs) ameliorate injury and accelerate repair in many organs, including the kidney, although the reparative mechanisms and interaction with macrophages have not been elucidated. This study investigated the reparative potential of human bone marrow-derived MSCs and traced their homing patterns following administration to mice with ischemia-reperfusion (IR) injury using whole body bioluminescence imaging. The effect of MSCs on macrophage phenotype following direct and indirect coculture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 72 publications
10
94
0
2
Order By: Relevance
“…Moreover, our results showed that the liver was the main organ retaining exogenous macrophages (Fig. 3B-C), as previously described by other authors[14, 19, 20]. Once the detection of the infused macrophages in the kidney was confirmed, we next isolated them by cell sorting two days after the infusion to analyze their phenotype and function.…”
Section: Resultssupporting
confidence: 82%
“…Moreover, our results showed that the liver was the main organ retaining exogenous macrophages (Fig. 3B-C), as previously described by other authors[14, 19, 20]. Once the detection of the infused macrophages in the kidney was confirmed, we next isolated them by cell sorting two days after the infusion to analyze their phenotype and function.…”
Section: Resultssupporting
confidence: 82%
“…This is also supported by the in vitro finding that macrophages stimulated with MSCs show an increase in the M2 phenotype, and the transfer of MSC-cocultured macrophages into the macrophage depletion mice inhibits renal injury [41]. Consistently, the role of MSCs in M2 polarization was also confirmed in IRI [42]. …”
Section: Regulatory Mechanisms Of Macrophage Polarization In Kidney Dmentioning
confidence: 58%
“…As a result, these cells can be efficient carriers for anti-cancer therapeutic agents' delivery to target tissue, a critical feature of achieving therapeutic efficacy. Moreover, these cells have shown a strong chemotactic response to injuries (14,41). Thus, OECs and BMS cells may be used as tumor-selective targeting carriers for the delivery of anti-cancer agents and cytotoxic genes toward the tumor.…”
Section: █ Discussionmentioning
confidence: 99%